PENYULUHAN FLOUR ALBUS DALAM PENCEGAHAN DAN PENANGANAN PADA REMAJA PUTRI SEBAGAI UPAYA DETEKSI DINI - Apriyani, Magdalena Tri Putri; Rini, Ageng Septa (STIKes Santa Elisabeth Medan, 2023)
Fluor albus (leukorrhea) or commonly referred to as vaginal discharge is excessive fluid discharge from the feminine area. Fluor albus is the most common gynecological symptom that occurs in pre-pubertal girls and teenagers. Vaginal discharge can be normal or abnormal vaginal discharge. Physiological vaginal discharge (normal ) is the discharge of excessive fluid/mucus from the vagina which is white or clear, odorless, painless/itchy, and smooth. Meanwhile, pathological (abnormal) vaginal discharge is the discharge of fluid/mucus from the vagina with an abnormal color change (yellow-green or white -grey), cloudy, and accompanied by pain, odor or itching (Kurniadi, 2017). The aim of this service is to increase knowledge among young women in recognizing flour albus. This counseling was carried out to 45 participants and they received the information well as proven by the correct answers after being given the counseling, namely 97%.